Cisplatin plus docetaxel combination in the first-line treatment of metastatic non-small cell lung cancer - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2010)
Aims. To evaluate activity and toxicity of cisplatin plus docetaxel combination in the first-line treatment of chemotherapy-naive patients with metastatic non-small cell lung cancer. Patients and methods. Between October 2004 and July 2008, 186 patients with metastatic non-small cell lung cancer treated with first-line cisplatin plus docetaxel were retrospectively evaluated in 7 centers. The chemotherapy schedule consisted of cisplatin, 75 mg/m(2) iv infusion, and docetaxel, 75 mg/m(2) iv infusion on day 1, every 3 weeks. Results. Median age was 56 years (range, 28-75). Eighteen patients (9.7%) were females and 168 (90.3%) were males, with a median ECOG performance status of 1 (range, 0-2). A total of 833 cycles of chemotherapy was administered (median, 4 cycles; range, 1-6). Two patients (1.1%) achieved clinical complete response, 77 patients (41.4%) partial response, and 66 patients (35.5%) stable disease. Median time to disease progression was 6 months (95% CI, 5.54-6.46). Median overall survival was 14.6 months (95% CI, 11.47-17.73). One- and 2-year overall survival was 55.2% and 19.7%, respectively. The most common grade 3-4 hematological toxicities were neutropenia (n = 32, 17.2%) and anemia (n = 4, 2.2%). Conclusions. The cisplatin plus docetaxel combination was effective and safe in the first-line treatment of patients with metastatic non-small cell lung cancer. Free full text available at www.tumorionline.it
Keywords: cisplatin; docetaxel; metastatic non-small cell lung cancer; QUALITY-OF-LIFE; PHASE-III; RANDOMIZED-TRIAL; SURVIVAL; CHEMOTHERAPY; VINORELBINE; ETOPOSIDE